EKSPEKTASI MASYARAKAT TERHADAP MAN 1 GORONTALO - Abdul Rahman Arsyad (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
Madrasah claimed to have a nuanced management Islamiyah is still small comparedwith the number of public schools. However, it is now used as the first choice for thecommunity. The study used a combination of methods (mixed methods), quantitativeand qualitative in describing the social reality of the expectations of parents ofstudents send their children to madrassas.Education and profession has no effect on the knowledge society (academics andordinary people) about the existence of madrassas. Learning religious education andreligious (beliefs and morals) are highly relevant to teens, wherein the container is afortress that are not easily contaminated from negative influences. The developmentof educational facilities and teaching materials religion and religious influencelearning quality improvement that the alumni had a great chance keperguruanunacceptable high